The "old forest reserve" and the road to Tolstojs grave at Jasnaja Poljana. From: Bro 605/4 fol, nr.50 (1958)
The "old forest reserve" and the road to Tolstojs grave at Jasnaja Poljana. From: Bro 605/4 fol, nr.50.